ASSESSING THE INFLUENCE OF PERFORMANCE MANAGEMENT SYSTEMS ON ORGANIZATIONAL EFFICIENCY IN THE DEVELOPMENT SECTOR OF ARUNACHAL PRADESH - Srivastava, Shalini; Pathak, Vivek Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Through the course of this research, the impact of performance management systems (PMS) on the effectiveness of organizations operating within the development sector of Arunachal Pradesh was investigated. In this study, a descriptive and analytical methodology was utilized, and the participants consisted of 150 individuals from 12 different development organizations. These organizations included both governmental and non-governmental organizations. Primary data were gathered through the use of structured questionnaires, interviews, and focus group discussions. Secondary data, on the other hand, were obtained from the records of the institution. For the purpose of determining the nature of the connections that exist between PMS components and organizational effectiveness, statistical methods such as descriptive statistics, Pearson's correlation, and multiple regression analysis were utilized. According to the findings, the establishment of goals, the provision of regular feedback, and the provision of training and development all greatly contributed to the improvement of the performance of the institution. The effectiveness of reward and recognition systems, on the other hand, was not particularly high. In addition, qualitative insights brought to light the significance of maintaining transparency and fairness, as well as continuously enhancing capability. The research came to the conclusion that a project management system (PMS) that is both integrated and well-structured is essential for improving organizational efficiency, accountability, and service delivery in development organizations that operate in resource-sensitive regions such as Arunachal Pradesh.